Motor Coordination in Schoolchildren Aged 6 to 11 in Northwestern Spain. A Cross-Sectional Study Based on Age and BMI - Ricardo Fernández-Vázquez; Rubén Navarro-Patón; Martín Barcala-Furelos; Javier Cachón-Zagalaz; Marcos Mecías-Calvo (Children)
Background/Objectives: A large percentage of schoolchildren are children with overweight or obese, and weight gain over time increases the risk of poor health later in life. Motor coordination may be a protective factor, enabling young people to participate in healthy physical activities. However, it is unknown when the relationship between motor coordination and weight first emerges, nor whether it is evident across the body mass index (BMI) spectrum. The aim of this study was to explore what happens with coordination skills [i.e., locomotor coordination (LC), visuomotor coordination (VC), foot object control coordination (FOCC), hand object control coordination (HOCC), global motor coordination (GMC)] applying the 3JS battery, according to age (6 to 11 years) and BMI (normal weight, overweight or obesity) in a sample of 688 Primary Education participants (8.71 ± 1.66 years; 48.8% boys) from Galicia (Spain). Methods: To analyze the differences in the variables of the 3JS battery between age (6–11 years) and BMI (normal weight vs. overweight vs. obesity), they were evaluated using a multivariate analysis of covariance (MANCOVA), introducing the sex category (boy-girl) as a covariate to avoid possible confounding factors. Results: After the application of the 3JS Battery, statistically significant differences were observed depending on age [LC (p < 0.001); VC (p < 0.001); FOCC (p < 0.001); HOCC (p < 0.001); GMC (p < 0.001)] and BMI [LC (p < 0.001); VC (p = 0.008); HOCC (p < 0.001); GMC (p < 0.001)]. No statistically significant differences were found in the interactions between age and BMI (p > 0.05). Conclusions: Locomotor coordination increases progressively with age, both globally and in each of the manifestations, and this is greater the older the schoolchildren are. Schoolchildren with normal weight compared to schoolchildren with overweight or obesity have better global motor coordination, locomotor coordination, global control of objects, and control with the hand.